Gene expression and variation in social aggression by queens of the harvester ant Pogonomyrmex californicus. Issue 15 (30th June 2016) - Helmkampf, Martin; Mikheyev, Alexander S.; Kang, Yun; Fewell, Jennifer; Gadau, Jürgen
Abstract: A key requirement for social cooperation is the mitigation and/or social regulation of aggression towards other group members. Populations of the harvester ant Pogonomyrmex californicus show the alternate social phenotypes of queens founding nests alone (haplometrosis) or in groups of unrelated yet cooperative individuals (pleometrosis). Pleometrotic queens display an associated reduction in aggression. To understand the proximate drivers behind this variation, we placed foundresses of the two populations into social environments with queens from the same or the alternate population, and measured their behaviour and head gene expression profiles. A proportion of queens from both populations behaved aggressively, but haplometrotic queens were significantly more likely to perform aggressive acts, and conflict escalated more frequently in pairs of haplometrotic queens. Whole‐head RNA sequencing revealed variation in gene expression patterns, with the two populations showing moderate differentiation in overall transcriptional profile, suggesting that genetic differences underlie the two founding strategies. The largest detected difference, however, was associated with aggression, regardless of queen founding type. Several modules of coregulated genes, involved in metabolism, immune system and neuronal function, were found to be upregulated in highly aggressive queens. Conversely, nonaggressive queens exhibited a striking pattern of upregulation in chemosensory genes. Our results highlight that the social phenotypes of cooperative vs. solitary nest founding tap into a set of gene regulatory networks that seem to govern aggression level. We also present a number of highly connected hub genes associated with aggression, providing opportunity to further study the genetic underpinnings of social conflict and tolerance.